Integrasi Komunikasi Organisasi dan Teknologi Informasi dalam Pencegahan Fraud JKN: Sebuah Scoping Review - Fika S. Khayan; Rini Sudarmanti (Universitas Malahayati, 2026)
ABSTRACT Fraud in the implementation of the National Health Insurance (JKN) services is a serious challenge in Indonesia. Preventing fraud needs to be strengthened through a systemic organizational communication strategy based on digital technology, especially by improving information technology in hospitals, such as Hospital Management Information Systems (SIMRS) and the E-claim application. Previous studies have highlighted the role of these technologies in detecting fraud, but few have examined the role of internal communication across units in supporting the effectiveness of digital interventions for reporting and detecting fraud. This article uses a Scoping Review based on the Arksey O’Malley (2005) framework and PRISMA-ScR reporting to map the literature on the integration of organizational communication and information technology in preventing fraud in JKN at hospitals. The thematic analysis based on CIMO (Context, Intervention, Mechanism, and Outcome) shows that the success of anti-fraud technology strongly depends on systemic internal communication mechanisms and an open organizational culture. The main recommendation is a fraud prevention strategy that integrates technology and organizational communication to achieve sustainable transparency and accountability. Keywords: Organizational Communication, JKN Fraud, Information Technology, SIMRS. ABSTRAK Fraud atau kecurangan dalam pelaksanaan layanan Jaminan Kesehatan Nasional (JKN) menjadi tantangan serius di Indonesia. Pencegahan fraud perlu diperkuat melalui strategi komunikasi organisasi sistemik berbasis digital, terutama dengan peningkatan teknologi informasi di rumah sakit, seperti SIMRS (Sistem Informasi Manajemen Rumah Sakit) dan aplikasi e-claim. Terdapat studi penelitian yang menyoroti peran teknologi tersebut dalam mendeteksi fraud, namun belum banyak yang mengkaji peran komunikasi internal lintas unit dalam mendukung efektivitas intervensi digital pada proses pelaporan dan deteksi fraud. Artikel ini menggunakan Scoping Review dengan kerangka Arksey O’Malley(2005) dan pelaporan PRISMA-ScR untuk memetakan literatur tentang integrasi komunikasi organisasi dan teknologi informasi dalam pencegahan fraud JKN di rumah sakit. Analisis tematik berbasis CIMO (Context, Intervention, Mechanism dan Outcome) menunjukkan bahwa keberhasilan teknologi anti-fraud sangat tergantung pada mekanisme komunikasi internal dan budaya organisasi terbuka. Rekomendasi utama adalah strategi pencegahan fraud yang mengintegrasikan teknologi dan komunikasi organisasi untuk mencapai transparansi serta akuntabilitas yang berkelanjutan. Kata Kunci: Komunikasi Organisasi, Fraud JKN, Teknologi Informasi, SIMRS.